Kinerja Dilihat dari Perspektif Kepemimpinan Militer dan Budaya Organisasi - Yogaswara, Andrey Satwika; Disman, Disman; Ahman, Eeng; Nugraha, Nugraha (Image : Jurnal Riset Manajemen, 2023)
This study aims to determine the role of military leadership and organizational culture on leaders' performance in the TNI AD Military Police unit. The approach used is descriptive verification with multiple regression methods. The population in the study were 69 POMDAM and DENPOM commanders throughout Indonesia. Data collection used a questionnaire distributed via google forms in one data collection (cross-sectional method). Military leadership variables are measured by task-oriented, relationship-oriented, change-oriented, and external dimensions. Organizational culture variables are measured using the dimensions of individual behavior, norms, dominant values, philosophy, applicable regulations, and organizational climate. Meanwhile, the TNI Commander's regulations measure the leader's performance, including quantity, quality, creativity, cooperation, initiative, and personal qualities. The findings show that military leadership and organizational culture significantly affect leadership performance, partially or simultaneously. Military leadership, which is a projection of the personality and character of a leader to make his subordinates do what is asked, can explain performance. Oath-based military culture includes matters such as commitment, values, and behavior which are elements in the culture that play a role in improving the performance of every level of personnel in the organization.